THE PSYCHOLOGY OF AUDIENCE AWARENESS IN THE COMPOSING PROCESS: THE CASE FOR NOVICE AND EXPERT WRITERS - Rahmat, Noor Hanim; Jauhari, Nadiah H; Othman, Noor Ahnis; Ramli, Nor Fazlin (PEOPLE: International Journal of Social Sciences, 2018)
Writing is seen as a social cognitive process by the writer and teaching it will have to focus on the social context. Writers write so that their ideas can be conveyed and understood by their readers. This means writers write with the audience in mind-all the time. Different writers address their audience in different ways. The objective of this research is to explore the strategies used by different types of ESL writers to address their audience. Specifically, this case study focuses on the audience awareness strategies through the use of interactive and interactional discourse. Two writers were used as subjects in this qualitative study. Both qualitative and quantitative data were analysed. Findings reveal different writers use different metadiscourse to communicate with their audience. Results of this study bear interesting implications in the teaching and learning of academic writing in the ESL classroom.